Minimum wages and insurance within the firm - Effrosyni Adamopoulou; Francesco Manaresi; Omar Rachedi; Emircan Yurdagul (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
Minimum wages generate an asymmetric pass-through of firm shocks across workers. We establish this result leveraging employer-employee data on Italian metalmanufacturing firms, which face different wage floors that vary within occupations. In response to negative firm productivity shocks, workers close to the wage floors experience higher job separations but no wage loss. However, the wage of high-paid workers decreases, and more so in firms with higher incidence of minimum wages. A neoclassical model with complementarities across workers with different skills rationalizes these findings. Our results uncover a novel channel that tilts the welfare gains of minimum wages toward low-paid workers.
Keywords: E24; E25; E64; J31; J38; J52; 330; Firm productivity shocks; pass-through; employer-employee data; skill complementarities; incomplete-market model